The OHADA Accounting System facing the challenges of Green Finance: A conceptual Analysis (Journal of Academic Finance, 2020)
Environmental issues and awareness of climate change are pushing companies today to adapt to a new context, limiting their harmful emissions and investing in sustainable projects that respect the environment. Thus, they can benefit from manna of financing, called green financing, adapted to their commitment. The emergence of this new method of financing challenges both professionals and researchers. As such, the purpose of this work is to make a conceptual analysis of the contribution of the OHADA accounting system in the reduction of information asymmetry under the green financing contract. To do this, two theories have been mobilized: signal theory and transaction cost theory. In a first, based on signal theory, it appears that the OHADA accounting system can be a signaling tool capable of acting on the risk of adverse selection. Secondly, based on the theory of transaction costs, it can be considered as an institutional arrangement equivalent to internalization capable of reducing the risk of moral hazard and the opportunism of managers in the context of the financing contract green.Key Words: OHADA Accounting System, Information Asymmetry, Green Funding
Keywords: OHADA Accounting System, Information Asymmetry, Green Funding